Research on the Impact of New Asset Management Regulations on Trade Credit Financing - Liao, Songmao (Transactions on Economics, Business and Management Research, 2024)
Financing has always been a difficulty for small and medium-sized enterprises (SMEs) and private enterprises in our country. After new asset management regulations were introduced, shadow banking has been inhibited and enterprises turned to trade credit financing. This paper uses the panel data of China’s A-share listed companies from 2013 to 2022 as a sample to explore the impact of new asset management regulations on trade credit financing of enterprises by DID model. The results show that the new regulation promotes the trade credit financing. Improving financing constraints is the way for the policy to influence trade credit financing. In areas where shadow banking is developed or companies with less collateral, the policy promote trade credit financing more vigorously. It is suggested that enterprises should strengthen communication with each other, and the government should guide commercial banks to establish a new loan evaluation system and correctly guide the healthy development of shadow banking.